Accurate Modeling and Control System Design for a Spherical Radial AC HMB for a Flywheel Battery System - Weiyu Zhang; Zhen Wang (Energies, 2023)
Different from common cylindrical magnetic bearings, the spherical radial AC HMB has obvious advantages in suppressing the gyroscopic effect, thus it is very suitable for application in flywheel battery systems. In this study, a precise mathematical model of suspension forces is deduced adopting wide-area and universal modeling theories in detail for the spherical radial AC HMB. Different from the traditional Maxwell tensor method based on a cylindrical two-dimensional coordinate system, the improved Maxwell tensor method based on a spherical coordinate system has a wider range and versatility. Then, the detailed explanation about the accuracy, wide-area and universality are given. Further, based on the model, the control system is designed, which includes the overall schematic, hardware and software designs. Finally, stiffness and performance tests are conducted. The good results of the stiffness tests indicate the error between the proposed model and the force-deflection stiffness test results is less than 2.8%. The good performance test results show that, based on the established model and control system, the rotor will soon return to equilibrium position under the disturbance of vehicle action.